English as A Lingua Franca: How It Is Interpreted and Implemented in EFL Classroom - Ramadhan, Rizki; Siregar, Yuniar D A (IJET (Indonesian Journal of English Teaching), 2018)
People all around the globe has recognized that English is now used as its lingua franca. It means that English has been used as a means to communicate in every aspect of situation among people who do not share the same first language. This phenomenon is being analyzed by linguists, so that the term English as an International Language, English as a Lingua Franca, or World English(es) emerge and become an interesting topic to be discussed, especially how teacher should interpret and how it could affect their belief and their behavior in teaching and learning classroom. However, there are found that some English teacher is still unfamiliar with this term and how it can influence teaching behavior. This article aims to accommodate those missing part and gives more enlightenment to the English teacher about ELF phenomenon.